Understanding generation Z: what working conditions are the most important motivating factors for generation Z in Bangladesh - Himi, Taki Nawer (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.